Cognitive Control along the Language Spectrum: From the Typical Bilingual Child to Language Impairment - Marton, Klara; Gehebe, Thorfun; Pazuelo, Lia (Seminars in Speech and Language, 2019)
Cognitive control refers to the ability to perform goal-directed behaviors in the presence of other compelling actions or in the face of habitual practices. Cognitive control functions play a critical role in children's language processing and literacy development. In recent years, many clinicians have expanded their assessment and treatment to target specific cognitive skills. Our goal is to provide a review of recent findings on cognitive control functions in children with different language status (i.e., monolingual and bilingual children with and without language impairment). While children with language impairment show performance deficits in specific cognitive functions (e.g., working memory updating and interference control), typically developing bilingual children often outperform their monolingual peers in cognitive control tasks. However, the relationship between bilingualism and cognitive control has been controversial. Several factors that influence these variations are discussed. Given the findings on the joint impact of bilingualism and language impairment on cognitive control functions, we identify conditions in which bilingualism attenuates the negative effects of the language deficit and conditions in which language impairment has a stronger effect than bilingualism. Critical issues of bilingual assessment, suggestions, and future directions are discussed.
Keywords: cognitive control; specific language impairment; bilingualism; language proficiency